Determination of citrus juice coumarins, furanocoumarins and methoxylated flavones using solid phase extraction and HPLC with photodiode array and fluorescence detection. (15th January 2019) - Li, Gui-Jie; Wu, Hou-Jiu; Wang, Yu; Hung, Wei-Lun; Rouseff, Russell L.
Highlights: Rapid extraction of 3 biologically active chemical families from citrus juices. 16 Major citrus methoxyflavones, coumarins and psoralens separated in 30 min. UV/fluorescence peak ratios provided unique information for identifications. Some juices hydrolyze epoxides, form dihydroxides of different biological activity. Two coumarins identified in orange juice for the first time, confirmed by LC-MS-MS. Abstract: A synergistic combination of analytical techniques was developed for the simultaneous determination of the three most biologically active chemical families in citrus juices: methoxylated flavones, coumarins, and furanocoumarins. No rapid methodology has been available to determine them together. A solid phase extraction concentrated these groups and a ternary reverse phase HPLC gradient completely resolved them from other juice components. Two coumarins, isomeranzin and osthole, were identified in a sweet orange ( C. sinensis ) cultivar, Changyecheng, for the first time. Pummelo juice was characterized by coumarin and furanocoumarin epoxides such as meranzin and epoxybergamottin. No epoxides were observed in the more acidic juices. Added furanocoumarin epoxides hydrolyzed rapidly in the most acidic juices. The ratios of the UV peak areas at 320 nm to the fluorescence emission peaks as well as the ratio of fluorescence emission peaks at 450–400 nm could be used to identify chromatographic peaks.